Strengthening dual-phase Mg-Li alloy through precipitation control - Yuchuan Huang; Fangzhou Qi; Jiawei Sun; Yangyang Xu; Youjie Guo; Jiaxin Yu; Lingfan Yi; Xinmiao Tao; Guohua Wu; Wencai Liu (Materials Research Letters)
Inherent low strength is the major limitation of Mg-Li alloys. Through precise control of precipitates, the cast Mg-8Li-3Al-2Zn alloy obtained a high specific ultimate tensile strength of 213 kN·m·kg−1. Precipitates evolution during non-isothermal aging was investigated: strip-like Mg3(Al, Zn) in β-Li → globular Mg3(Al, Zn) in β-Li →Mg/Li(Al, Zn) core–shell and nanoscale rod-like Mg3(Al, Zn) in β-Li + Laves phase in α-Mg. The short-term high-temperature aging results in the precipitation of Laves phase in α-Mg and the formation of nanoscale rod-like Mg3(Al, Zn) and Mg/Li(Al, Zn) core–shell phase in β-Li, achieving synergistic strengthening of the dual matrix phases.